2015
DOI: 10.5604/16652681.1171776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alpha-fetoprotein as a screening marker for hepatocellular carcinoma in hepatitis prevalent areas

Abstract: The objective of this study was to establish modified cutoff values of serum alpha-fetoprotein (AFP) according to hepatitis status. While AFP is used as a serum marker in the diagnosis or monitoring of hepatocellular carcinoma (HCC), its use as a screening method to the general population is controversial. We evaluated its screening performance in a hepatitis prevalent East Asian population, and suggest different cutoff values according to the individual's hepatitis status. We evaluated the performance of AFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In this case, a prospective and large-scale clinical trial would be necessary to determine the sensitivity and specificity according to the follow-up time. However, the current positive predictive value (PPV) of 17% from the validation cohort was significantly higher than previously obtained with screening for AFP levels alone (17). The PPV could be further improved if a second HCCscreen test is provided to the cases positive in the first test.…”
Section: Discussionmentioning
confidence: 68%
“…In this case, a prospective and large-scale clinical trial would be necessary to determine the sensitivity and specificity according to the follow-up time. However, the current positive predictive value (PPV) of 17% from the validation cohort was significantly higher than previously obtained with screening for AFP levels alone (17). The PPV could be further improved if a second HCCscreen test is provided to the cases positive in the first test.…”
Section: Discussionmentioning
confidence: 68%
“…Diagnosis of HCC is usually dependant on image techniques, blood indicators, and histopathology. 1,[6][7][8][9] These methods improve the detection of HCC to some degree, but the sensitivity and specificity for HCC screening remain unsatisfactory. At the same time, identification of the pathogenic mechanisms involved in HCC and development of useful prognostic biomarkers as well as novel targeted therapeutic strategies are the urgent clinical necessities, so we hope to find some new diagnostic biomarkers that can further improve the early detection of HCC in at-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several studies have identified that there are many serum biomarkers that have the potential to assist the early diagnosis of HCC ( 1 , 8 , 9 ). α-fetoprotein (AFP) levels were detectable in the blood of many patients with advanced HCC ( 10 , 11 ). However, high AFP levels were unreliably detected in patients with early stage HCC.…”
Section: Introductionmentioning
confidence: 99%